Validation of Real‐time PCR Assays for Bioforensic Detection of Model Plant Pathogens1. Issue 2 (21st November 2013) - James, Mindy; Blagden, Trenna; Moncrief, Ian; Burans, James P.; Schneider, Katherine; Fletcher, Jacqueline
Abstract The U.S. agricultural sector is vulnerable to intentionally introduced microbial threats because of its wide and open distribution and economic importance. To investigate such events, forensically valid assays for plant pathogen detection are needed. In this work, real‐time PCR assays were developed for three model plant pathogens: Pseudomonas syringae pathovar tomato, Xylella fastidiosa, and Wheat streak mosaic virus. Validation included determination of the linearity and range, limit of detection, sensitivity, specificity, and exclusivity of each assay. Additionally, positive control plasmids, distinguishable from native signature by restriction enzyme digestion, were developed to support forensic application of the assays. Each assay displayed linear amplification of target nucleic acid, detected 100 fg or less of target nucleic acid, and was specific to its target pathogen. Results obtained with these model pathogens provide the framework for development and validation of similar assays for other plant pathogens of high consequence.